Depsipeptide dendrimers - Kress, Jürgen; Rosner, Alexander; Hirsch, Andreas (Chemistry - A European Journal, 2000)
The convergent synthesis of a new class of chiral dendrimers is described. Owing to their structural resemblance to depsipeptides they are called depsipeptide dendrimers. The ex-chiral pool synthesis starts from (R,R)-, (S,S)-, and meso-tartaric acid as branching units and dipeptides or tripeptides consisting of glycine, (L)-alanine, and (L)-leucine as chiral-spacer building blocks. The key intermediates for the convergent assembly of such depsipeptide dendrimers are the peptide-tartaric acid conjugates 13a,b, 19a,b, 25, and 27, which contain either an unprotected C terminus of the peptide chain (13a,b, 25) or two unprotected hydroxy groups within the tartaric acid termini. Dendra up to the third-generation, by using different combinations of stereoisomeric building blocks, were synthesized and completely characterized. Since this construction principle of chiral depsipeptide dendrimers allows for a wide variation of the length, the primary structure of the peptide spacer, and the configuration of both the amino acid and the tartaric acid moieties, access to new combinatorial libraries is conceptually provided.